The Association Between Glaucoma Severity and Anxiety And Depression in Glaucoma Patients at DR. Soetomo General Hospital, Surabaya, Indonesia - Milan Samudera, Raditya Effendi; Komaratih, Evelyn; Konginan, Agustina; Primitasari, Yulia (Rifa'Institute, 2025)
Introduction: Glaucoma is a chronic progressive disease and one of the leading causes of blindness worldwide. Vision loss due to glaucoma affects not only the physical aspect but also has an impact on the patient’s mental health. Poor mental condition may influence the success of therapy and reduce the patient’s quality of life. Objective: The objective of this study is to examine the association between the severity of glaucoma and anxiety and depression in the Eye Outpatient Unit of RSUD Dr. Soetomo Surabaya, Indonesia. Method: A cross-sectional study was conducted involving 50 glaucoma patients at the Ophthalmology Outpatient Unit of Dr. Soetomo General Hospital, Surabaya. Mental health status was assessed through interviews using the Hospital Anxiety and Depression Scale (HADS). The Spearman’s rho correlation test was applied to evaluate the association between glaucoma severity and the presence of anxiety and depression. Result and Discussion: Primary Open-Angle Glaucoma (POAG) was the most prevalent type, and most cases were bilateral. Statistical analysis demonstrated a significant correlation between glaucoma severity and anxiety (r = 0.599), between glaucoma severity and depression (r = 0.520), and also between anxiety and depression (p = 0.001). Conclusions: The severity of glaucoma is related to anxiety and depression